Continuity of Household Surveys after the Coronavirus Disease (COVID-19) Pandemic - Economic Commission for Latin America; the Caribbean (United Nations, 2021)
In the context of the global coronavirus disease (COVID-19) pandemic, the Economic Commission for Latin America and the Caribbean (ECLAC) is preparing a series of short publications with key policy recommendations for this period. This note, the third on household surveys, offers some considerations regarding the continuity of this type of statistical instrument in a context of initial lifting of the restrictions on movement in the region that were put in place to contain the spread of the pandemic.